Atividades de software e serviços de informática no Brasil: desempenho econômico e evolução (2010-2019) - Jesus, Ana Carolina Navegantes de (Universidade Federal de São Carlos, 2024)
Considering the importance in the current context of digitalization of the economy and industry 4.0, as well as the differentiated nature of software, marked by its pervasiveness and transversality, this research presents results referring to the primary dimension of software activities and IT services in the country and secondary dimension (other sectors of the economy), from 2010 to 2019. Data from the IBGE Annual Services Survey were analyzed and, through them, indicators such as Net Operating Revenue, employed personnel, net revenue from services provided, among others, of the industry were verified, regarding software and IT services, considering the corresponding CNAE's and also the methodology proposed by Diegues and Roselino (2011), which considers the occupational families of software activities, in order to evaluate the relevance of the secondary dimension in numbers. It was concluded that there is significant importance of the software sector in the country's economic scenario, and that there are still possible margins for growth in these activities outside the industry, too, even with considerable participation in the period.
Software and computer services activities in Brazil: economic performance and evolution (2010-2019)
Keywords: Software; Indústria de Software; Pervasividade; Transversalidade; Software Industry; Pervasiveness; Transversality; CIENCIAS SOCIAIS APLICADAS::ECONOMIA